2010
DOI: 10.1042/cbi20090074
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II increases mRNA levels of all TGF‐β isoforms in quiescent and activated rat hepatic stellate cells

Abstract: AII (angiotensin II) is a vasoactive peptide that plays an important role in the development of liver fibrosis mainly by regulating profibrotic cytokine expression such as TGF-beta (transforming growth factor-beta). Activated HSCs (hepatic stellate cells) are the major cell type responsible for ECM (extracellular matrix) deposition during liver fibrosis and are also a target for AII and TGF-beta actions. Here, we studied the effect of AII on the mRNA levels of TGF-beta isoforms in primary cultures of rat HSCs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…TGF- β is one of the most potent profibrogenic cytokines known for activated HSC. Ang II could increase mRNA levels of all TGF- β isoforms in rat HSC [39]. In our previous study, we found that Sal B could inhibit TGF- β 1 expressions and its receptor in fibrotic livers [14] and inhibit MAPK function in activated rat HSC [40].…”
Section: Discussionmentioning
confidence: 99%
“…TGF- β is one of the most potent profibrogenic cytokines known for activated HSC. Ang II could increase mRNA levels of all TGF- β isoforms in rat HSC [39]. In our previous study, we found that Sal B could inhibit TGF- β 1 expressions and its receptor in fibrotic livers [14] and inhibit MAPK function in activated rat HSC [40].…”
Section: Discussionmentioning
confidence: 99%
“…As it responds to Smad, the further matrix production in HSCs differs between acute and chronic injury (3). In addition to TGF-β, there are numerous other factors that exhibit profibrogenic effects on HSCs, such as retinoids and angiotensin II (4)(5)(6). During liver fibrosis, parenchymal injury and sustained inflammation generate a large panel of signals that induce the activation of quiescent HSCs.…”
Section: Different Cell Types In Liver Fibrosismentioning
confidence: 99%
“…HSCs are activated by reactive oxygen species, whereas fibrosis after liver injury is ameliorated in p47phox knockout mice [ 50 ]. In addition, in both activated and quiescent rat HSCs exposed to Ang II, the mRNA and protein levels of all TGF-β isoforms are upregulated via the ERK1/2- and Nox-dependent pathways, but independently of protein kinase C [ 52 ].…”
Section: The Ras In Hepatic Fibrosis and Portal Hypertensionmentioning
confidence: 99%